Effect of shoulder angle on physiological responses during incremental peak arm crank ergometry - Leicht, A. S.; Spinks, W. L. (Journal of Sports Sciences, 2007)
This study examined the effect of shoulder angle and gender on physiological and perceptual responses during incremental peak arm ergometry. Healthy adults (nine males, seven females) volunteered for the study and completed an incremental arm ergometry test on two separate occasions at two different shoulder angles (90° and 45°). Initial work rate was set at 16 W · min-1 and was increased progressively until exhaustion. Cardiorespiratory and perceptual responses were recorded at the end of each minute and compared using separate three-way (position × work rate × gender) repeated-measures analyses of variance. The systematic bias of peak responses was examined using separate two-way (position × gender) analyses of variance, while reproducibility of these parameters was explored using intraclass correlation coefficients, measurement bias/ratio, and 95% ratio limits of agreement. Despite a significantly greater peak heart rate for the 45° position, cardiorespiratory and perceptual responses were similar at peak exercise for both positions. Peak values for all variables, although similar, demonstrated similar and large inter-test variability for men and women. Reduction of the shoulder joint angle to 45° did not enhance peak work rate and peak oxygen consumption during seated upper body exercise. Due to the large inter-test variability, arm ergometry should be conducted using the same seated position.